1, 5-Dichloroethanoanthracene Derivatives As Antidepressant Maprotiline Analogs: Synthesis, DFT Computational Calculations, and Molecular Docking. (23rd September 2022) - Sultan, Mujeeb A.; Pillai, Renjith Raveendran; Alzahrani, Eman; Alsofi, Ahmed A.; Al-Qadhi, Sadam A.; Pashameah, Rami Adel
Abstract : The chlorinated tetracyclic 1, 5-dichloro-9, 10-dihydro-9, 10-ethanoanthracen-12-yl)-N-methylmethanamine 1, a maprotiline analog, has been synthesized via reduction and the Diels–Alder reaction followed by reductive amination of aldehyde 2 .1D-NMR (DEPT) and 2D-NMR (HSQC, DQF-COSY) techniques were recruited for structural elucidation in addition to HRMS. Density functional theory calculations were performed to identify the possible isomers of the intermediate compound aldehyde 2 ; these calculations were in good agreement with experimental results where aldehyde 2 could exist in three isomers with comparable energies. In addition, the side chain of this aldehyde 2 was extended via the Wittig reaction to obtain the unsaturated ester 5 that was subjected to selective olefinic catalytic hydrogenation to obtain the corresponding saturated ester 6 . Molecular docking simulation showed that all the compounds (1, 2, 5, and 6) have high antidepressant activities and form stable complexes with LeuT by inhibiting the neurotransmitter reuptake at the synapse and hence are good candidates as antidepressant drugs.